Modern technical methods in criminal evidence - Isseghli, Mohammed (The International tax journal, 2026)
This study addresses modern technical methods in criminal evidence. The use of modern scientific methods in proving crime has brought about a scientific revolution in the field of criminal evidence, which has made it necessary indeed imperative for criminal investigation officers to employ such methods in order to carry out the tasks entrusted to them in the best possible manner. Criminal investigation and the collection of evidence are among the foremost security activities aimed at confronting or eliminating newly emerging crimes, through the development of modern methods and means, as well as by equipping investigators with contemporary scientific and technological knowledge. Consequently, these technical methods have received growing attention from all nations. The Algerian state, like other countries around the world, has worked to adopt these modern technical methods in criminal evidence.